Utilization Of 'Aquajaya X Aquariset' Youtube Account As A Means Of Educating Aquascapers - Bimo Berdiarto Jokoniko; Megawati; Aditya Winarto (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This research starts from the evolving technological phenomenon which causes human activities that depend on the internet in several aspects of life. Advances in technology make helping people for easier to find and to get the entertainment they are want and even get information through social media. The development of technology has made many people explore hobbies, one of which is Aquascapse. The aquascape hobby is made into content that provides information or education for hobbyists. Based on this background, the researcher conducted a study on how AquaJaya x AquaRiset uses YouTube as an educational tool. Main of purpose in this study is to specify of using YouTube as educational advice for Aquascapers. To answer this study, researchers used the social information processing theory put forward by Littlejohn & Foss. This study used a descriptive qualitative method with semi-structured interviews with 1 resource person as the owner of the AquaJaya x AquaRiset YouTube account content, 3 sources as viewers and subscribers of the account. The conclution of this paper it can be concluded that the AquaJaya x AquaRiset YouTube account applies the values of social information processing theory and educational provision to Aquascapers.